The ambivalence of the virtual environment, space to educate or discriminate? (Research, Society and Development, 2024)
Digital technologies are so close to us, to everyday life that they have become naturalized. We live connected to social networks with the virtualization of instant information. They have played an important role in the teaching-learning process, especially in the pandemic context, however, they have their harmful side as they constitute a means of disseminating speeches that promote racism and social discrimination. The objective of this work was to carry out a critical analysis of digital technologies-social networks and their relationship with hate speech and racial discrimination. The research approach is quantitative. In the methodological path, an exploratory literature survey was carried out in databases: Electronic Publication System for Theses and Dissertations (TEDE), SciELO, Web of Science and Google Scholar using the descriptors: “Racism”, “Ethnic-Racial” , “Education”, “Social Networks”, “Prejudice”, “Algorithmic Bias”. The period from 2019 to 2023 was analyzed. The results indicated that despite the advantages in communication and educational expansion, they have been used to disseminate Fake News, hate speeches aimed at race, religion, gender, sexual orientation and incitement of physical and emotional violence, demonstrating its misuse. Therefore, it is crucial to debate and seek ways to ensure that ethics, democracy and security are complied with, including legal provisions such as Law No. 7,716/1989 related to crimes of racial prejudice and Law No. 12,965/2014 that establish rights and duties for the internet use in Brazil.